IT PROJECT MANAGEMENT ISSUES AT A LARGE CORPORATE BRAZILIAN BANK - Maccari, Emerson Antonio; Santos, Cássio Rogério; Batista, Denis Alberto; Tocura, Fábio Hiromitsu; Gutierrez, José (Future Studies Research Journal: Trends and Strategies, 2009)
The world financial segment is that which has most invested in products and services ground on Information Technology (IT). Brazilian banks follow this standard and have resorted to IT in an intense manner so as to foster competitiveness. Within this context, IT project management has become fundamental. In this study, the objective is to identify the impairments IT project management faces at a large Brazilian bank as of the perception of managers from both the IT and business-related areas. To this extent, a case study was undertaken and a semi-structured questionnaire was applied to 10 individuals that occupy leadership positions in the mentioned fields. Results indicate a lack of project management culture giving rise to: issues concerning IT project scope definition; communication setbacks between and within areas; absence of strategic alignment amongst involved areas; difficulty in perceiving an overall picture of projects; mismatch between project prioritization and delivery deadlines. Key-words: Project Management. Information Technology. Banking.